Automatic Feeding System in Pond Fish Farming Based on the Internet of Things - Tomy Chandra Mahendra; Sunardi Sunardi (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
One of the fish commodities consumed by the Indonesian people is catfish because it tastes good. Cultivation of catfish requires special attention regarding feeding because if it is not enough it can cause the fish to become cannibals, whereas if too much feed can cause disease. Therefore, it is necessary to monitor and control the provision of fish feed on a scheduled basis. This study aims to facilitate catfish farming in automatically scheduled fish feeding by utilizing the Internet of Things (IoT). This system is built using a NodeMCU micro controller which is connected to a Real Time Clock (RTC) sensor to adjust the feeding schedule. In addition, ultrasonic sensors are used to monitor feed conditions and servo motors to open and close the fish feed storage valve. This study succeeded in providing catfish feed automatically and on time according to a predetermined schedule, namely at 06.00 am, 12.00 noon, and 18.00 pm. Timing is based on the active hours of catfish. The system has also been successfully monitored and controlled remotely via the internet using the Blynk application. In addition, the system has also been able to identify the remaining feed reserves remaining in the storage container. This automatic feeding system has been operating in accordance with the purpose of the system, which is to provide fish feed according to the feeding hours of catfish so that cannibals or fish that are sick with ammonia are not found from leftover feed that is not eaten by catfish.